PERANAN KINERJA PERANGKAT DESA TERHADAP PENINGKATAN PENDAPATAN PETANI KOPI DESA PARSAORAN SIBISA - Firinta Togatorop; Doris Yolanda Saragih (Politeknik Bisnis Indonesia, 2019)
One of the spearheads of the local government system is the village government which consists of village officials that work together and touch each other and deal directly with the community. This research was conducted in the village of Parsaoran Sibisa, Ajibata District, Toba Samosir Regency. The background of this research is that the village of Parsaoran Sibisa is one of the priority areas for research where there are differences in productivity of coffee yields in the villages of Parsaoran Sibisa and Motung where the coffee yields of Motung Village are much better and the villagers are able to process coffee and marketing coffee yields well while the village of Parsaoran Sibisa has not been able to even though the two villages are still one district. This study aims to determine and analyze the role of the Village Apparatus in an effort to increase the income of coffee farmers who are approximately 75% of the total population of Parsaoran Sibisa village are farmers coffee as well as knowing the factors that drive and hinder village officials in empowering the community in the village of Parsaoran Sibisa, Ajibata District, Toba Samosir Regency.